Mondeguina, a new genus for Apatetris mediterranella Nel & Varenne, 2012, with description of a new species from Portugal (Lepidoptera, Gelechiidae) - Martin F. V. Corley; Jorge Rosete; Sónia Ferreira (Nota Lepidopterologica, 2020)
Following the discovery of a new species on the western coast of Portugal which is closely related to Apatetris mediterranella Nel & Varenne, 2012, the generic placement of both species is considered in relation to other genera within the Apatetris complex resulting in the description of a new genus, Mondeguina.